Pengaruh Grain Size Arang Aktif dari Bahan Limbah Industri Sagu Aren terhadap Penyerapan Polutan Limbah Batik - Kuncoro Diharjo, Sudarja , Novi caroko , (Jurnal Semesta Teknika, 2011)
Sago palm industries leave large amount of wood waste that is about 30% of the volume of tree trunks, 20% in large size which can be used for the handcraft and about 10% in small-size which only wasted. On the other hand, batik industries produce hazardous and toxic waste (B3), that should be neutralized since this liquid waste are bad smell and Â hard color, and even toxity Â (contain various kinds of chemical elements and heavy metals such as Mercury (Hg), Lead (Pb), Chromium (Cr), Cadmium (Cd), and Copper (Cu)) and if the elements are absorbed by human body exceeds the threshold point, it would be dangerous. Therefore, experiment on activated carbon engineering and its use in adsorbing the B3 batik liquid waste is urgently required. Â The main objective of the experiment is to know the adsorbsion effectivity of activated carbon in adsorbing the batik liquid waste. The main material used in producing activated carbon is waste palm tree trunks. The main material is heated to be charcoal in retort for about 5 hours, temperature around 500 Âº C. Furthermore, charcoal is crushed finely and screened in sizes of mesh 25, 35 and 50. Carbon powder then chemically activated using H2SO4 solution by heating in 500 ËC for about 30 menutes. Finally this activated carbon used for adsorbing the hard colour and heavy metal (Pb, Cr, Cd) in the batik waste water. This research concluded that the sago aren industrial waste may be an alternative material for activated carbon which is effective in adsorbing the hard colour and hazardous heavy metal. Higher mesh size (grain size) of activated carbon give higher adsorbsion in colour and heavy metal. Activated carbon in mesh 25 adsorbedÂ 68.59% Cd, 16.65% Cr, and 100% Pb, mesh 35 adsorb Â 76.25% Cd, 37.55% Cr and Pb at 100%, while mesh 50 adsorb 81.61% Cd, 58,33% Cr, and 100% Â Pb.